The Specificity of Empirical Study of Speech of Patients with Motor Aphasia After Stroke - Milinchuk, V. I. (Psychological Prospects Journal, 2011)
The article focuses on procedures and results of a complex study of patients after stroke during their rehabilitation period. The results proved the efficiency of neuropsychological non-apparatus method of study of patients’ speech after stroke with motor aphasia. Firm correlation ties among patient’s speech and his/her general psychic activity have been revealed.